Clusterin increases mitochondrial respiratory chain complex I activity and protects against hexavalent chromium-induced cytotoxicity in L-02 hepatocytes. Issue 1 (15th November 2018) - Xiao, Yuanyuan; Zeng, Ming; Yin, Lirong; Li, Na; Xiao, Fang
Graphical Abstract: Abstract: Previous evidence revealed significant elevated liver cancer mortality in the areas where water was contaminated with hexavalent chromium [Cr(vi )], which highlighted that we should pay more attention to Cr(vi )-induced cytotoxicity in hepatocytes. We found that Clusterin (CLU) was up-regulated in Cr(vi )-exposed L-02 hepatocytes, but the role CLU played in Cr(vi )-induced cytotoxicity has never been explored. In the present study, we demonstrate Cr(vi ) targeted mitochondrial respiratory chain complex I (MRCC I) activity and induced reactive oxygen species (ROS) accumulation, which caused mitochondrial damage that was characterized by the increase of permeability transition pore (PTP) open rate, the collapse of mitochondrial membrane potential (MMP), and the release of apoptosis-inducing factor (AIF) and Cytochrome C (Cyt C) from mitochondria to cytoplasm, which then induced cell viability loss and increased aspartate transaminase (AST)/alanine transaminase (ALT) leakage. We reveal that Cr(vi ) may regulate CLU expression through the ROS-ataxia telangiectasia mutant (ATM)–insulin-like growth factor 1 (IGF-1) axis, and CLU expression was positively correlated to MRCC I activity. We further confirmed that CLU may regulate MRCC I activity via modulating its subunit nicotinamide adenine dinucleotide dehydrogenase (ubiquinone) Fe–S protein 3 (NDUFS3) expression. By the establishment of CLU over-expression cells, we found that over-expression of CLU alleviated Cr(vi )-induced MRCC I inhibition and further rescued cell viability loss and reduced AST and ALT leakage. Thus, we reached the conclusion that the CLU-induced increase of MRCC I activity protected against Cr(vi )-induced cytotoxicity. The present research will provide new experimental evidence for thoroughly clarifying the cytotoxicity and the carcinogenic mechanism of Cr(vi ).